Advances in haploidentical stem cell transplantation for hematologic malignancies. Issue 8 (2nd August 2016) - Montoro, Juan; Sanz, Jaime; Sanz, Guillermo F.; Sanz, Miguel A.
Abstract: One of the most important advances in allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the use of alternative donors and cell sources, such as haploidentical transplants (haplo-HSCT) from family donors. Several approaches have been developed to overcome the challenging bidirectional alloreactivity. We discuss these approaches, including ex vivo T-cell-depleted grafts with megadose of CD34 + cells, not requiring immunosuppression after allogeneic transplantation for graft-versus-host disease (GVHD) prophylaxis, and other strategies using unmanipulated T-cell-replete grafts with intensive immunosuppression or post-transplantation cyclophosphamide to minimize the GVHD. We also address the role of other strategies developed in the context of the haplo-HSCT platforms, such as ex vivo selective depletion of alloreactive donor T-cell subpopulations, infusion of antigen-specific T-cells against several pathogens, and infusion of regulatory T-cells, among other experimental approaches. Finally, some considerations about the selection of the most suitable donor, when more than one family member is available, are also addressed.